Multisystem Inflammatory Syndrome in a Patient with SLE - Chris Ching Lam Cheung; Kelly Kar Li Chan; Chiu Sum Chu; Chi Chiu Mok (Journal of Clinical Rheumatology and Immunology, 2023)
Coronavirus disease 2019 (COVID-19) was one of the most important infections in the past few years. Although most cases of COVID-19 are mild, serious complications may arise. The multisystem inflammatory syndrome (MIS) is a rare but severe, yet poorly understood complication of COVID-19. It was first described in childhood patients with COVID-19 (MIS-C) but is increasingly reported in adults. MIS-A may lead to diagnostic and therapeutic dilemma as its manifestations may mimic a flare of the underlying disease and the use of immunosuppressive therapy may further increase the risk of other infective complications in these patients. However, MIS-A has rarely been reported in patients with pre-existing autoimmune conditions. We hereby present a patient with systemic lupus erythematosus who developed severe MIS-A 6 weeks after a recent SARS-CoV-2 infection.